Causal Effects of Gut Microbiome on Tinnitus: A Mendelian Randomization Study - Zeng Q; Xie W; Dong H; Liu X; Shao S; Chen L; Zhang W (Journal of Multidisciplinary Healthcare)
Qiang Zeng,1 Wei Xie,2 Huaqian Dong,2 Xing Liu,1 Shuai Shao,1 Li Chen,1 Wenwen Zhang1 1School of Nursing, Guizhou University of Traditional Chinese Medicine, Guiyang, 550002, People’s Republic of China; 2Department of Nursing, the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, 550001, People’s Republic of ChinaCorrespondence: Wei Xie, Department of Nursing, the First Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, 550001, People’s Republic of China, Email 2817180455@qq.comBackground: Previous studies have identified a clinical association between gut microbiota (GM) and tinnitus; however, the potential causal relationship remains unclear. Therefore, we conducted a Mendelian randomization(MR) study to evaluate the potential causal effects of 412 gut microbiome features on tinnitus risk.Methods: In the study, we used pooled data from a genome-wide association study(GWAS) of gut microbes from a Dutch population. Summary statistics of tinnitus were drawn from the FinnGen R10 database. Inverse variance weighted, weighted median and MR-Egger were used to evaluate the potential causal link between GM and tinnitus.Results: The MR analysis revealed a negative association between the abundance of Parabacteroides distasonis and the risk of tinnitus (OR = 0.84, 95% CI: 0.74– 0.94, p = 0.003), suggesting a potential protective role. Conversely, positive associations were observed for Eggerthella (OR = 1.11, 95% CI: 1.01– 1.22, p = 0.032), Alistipes onderdonkii, and Lachnospiraceae bacterium 5-1-63FAA, all linked to increased tinnitus risk.Conclusion: Our findings suggest potential causal effects of specific gut microbial taxa and pathways on tinnitus, highlighting promising targets for prevention and treatment. However, further research is needed to validate these associations and clarify underlying mechanisms.Keywords: causal relationship, gut microbiota, Mendelian randomization, tinnitus